PENGARUH KEPEMILIKAN ULTIMAT TERHADAP NILAI PERUSAHAAN DIMEDIASI OLEH GREEN BANKING - Vincensius Reynold Tiodoris; I Putu Sugiartha Sanjaya (Faculty of Economics and Business, Universitas Warmadewa, 2026)
This study aims to provide empirical evidence on whether ultimate ownership influences firm value, with green banking serving as a mediating variable. Ultimate ownership is proxied by the cash flow rights leverage of the controlling shareholder. The data collection technique used in this study is purposive sampling, and the data consist of secondary data obtained from the annual reports and/or sustainability reports of banking companies listed on the Indonesia Stock Exchange from 2016 to 2023. The total number of observations with a 10% cutoff is 353. Data analysis was conducted using the Smart PLS 3 application. The results of this study indicate that, at the 10% cutoff level, cash flow right leverage negative impact on firm value. Cash flow right leverage does not affect green banking. Green banking positively influences firm value. But, green banking is unable to mediate the effect of cash flow right leverage on firm value.